APLIKASI BINARY INTEGER PROGRAMMING PADA PENYELESAIAN MASALAH LINE BALANCING - Gogor Arif Handiwibowo; Abdullah Shahab (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2006)
The proper assignment of work activities in a number of workstations in a production line system influences heavily the success of the production process. This problem is hitherto solved by trial and error or using the heuristic method which naturally does not ensure an optimal solution. The method of Binary Integer Programming is here proposed to solve this problem, which will ultimately guarantee an optimal solution. Optimization is carried out by formulating mathematical model programming with an objective function compelled to achieve the minimum number of workstations. This optimization is performed under the constraints of interdependency between work activities, cycle time, activities time, demand, and productive time available. The model is then employed in the production of women slipper. Optimization carried out by suitable software is proven able to assign each work activity in a specific workstation with an optimal efficiency. Comparison with the current performance shows a substantial efficiency increase.